Distance Learning “Sifajargoro”In the Era of the Covid-19 Pandemic - Abul Hasan Anshori; Sutama Sutama (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The temporary closure of all educational institutions as an effort to prevent the spread of an outbreak of Covid-19 worldwide has an impact on millions of students, including in Indonesia. Disturbances in the teaching and learning process directly between teacher and students as well as the termination of the assessment of learning have an impact on the psychological of students, causing a decrease in the quality of skills. This burden is the responsibility of all elements of education, in particular the government, in facilitating the continuity of schools for all stakeholders in education to conduct distance education. 'Sifajargoro" is present as an effort to help all education people, especially in bojonegoro district in distance learning in the COVID-19 pandemic era.abstract